Drug-induced pneumonitis following the administration of laninamivir octanoate: The first two reported cases. Issue 12 (December 2019) - Ogawa, Takunori; Tanaka, Kyuto; Ohgino, Keiko; Omori, Nao; Betsuyaku, Tomoko; Sayama, Koichi
Abstract: Laninamivir, a neuraminidase inhibitor (NAI), has been used for the treatment and prophylaxis of influenza A/B. To date, pneumonia has not been reported as an adverse effect of NAIs. Here, we report the first 2 cases of drug-induced pneumonitis after the administration of laninamivir octanoate (LO), a pro-drug of laninamivir. Case 1 reports a 20-year-old healthy woman presenting with LO-induced pneumonitis so severe that it was necessary for endotracheal intubation and administration of mechanical ventilator support. Steroids were used for the treatment of pneumonitis and rapid improvement was observed. Case 2 reports a 35-year-old healthy woman presenting with less severe LO-induced pneumonitis that improved without any treatment. In both cases, drug-induced lymphocyte stimulation tests (DLSTs) were positive. In the bronchoalveolar lavage (BAL) fluid, the proportion of eosinophils to lymphocytes was higher in Case 1. Conversely, the proportion of lymphocytes to eosinophils was higher in Case 2. Collectively, we determined 3 clinical issues: (1) LO could cause pneumonia; (2) BAL and DLST could be helpful in the diagnosis of LO-induced pneumonitis; and (3) LO-induced pneumonia could become severe, though steroids were effective in improving it.